2010
DOI: 10.1021/jp106582t
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Mediated Ion Exchange and Charge Reversal at Ionic Liquid Interfaces

Abstract: Room-temperature ionic liquids (ILs) exhibit a unique set of properties due to their charged character, presenting opportunities for numerous applications. Here, we show that the combination of charged surfactants with ILs leads to rich interfacial behavior due to the interplay between electrostatic and surface forces. Using traditional measures of surface activity and X-ray photoelectron spectroscopy (XPS), we find that sodium alkyl sulfates and alkyl trimethylammonium bromides are, indeed, surface-active at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(100 reference statements)
2
13
0
Order By: Relevance
“…At this point, we would like to bring into consideration an interesting observation that derives from recent surface tension and X-ray photoelectron spectroscopy experiments performed by Chen et al 48 on RTIL/air interfaces hosting ionic surfactants. The authors report an ionic exchange between surfactant counterions and RTIL ions of similar charge.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, we would like to bring into consideration an interesting observation that derives from recent surface tension and X-ray photoelectron spectroscopy experiments performed by Chen et al 48 on RTIL/air interfaces hosting ionic surfactants. The authors report an ionic exchange between surfactant counterions and RTIL ions of similar charge.…”
Section: Resultsmentioning
confidence: 99%
“…, with the degree of surface enrichment increasing with the alkyl chain length of the surfactant. 130 At the same time, the level of the surfactants' counterions, Na + or Br À , at the surfaces were below detection limits. Again this data indicates that the surface layers contain both cations and anions and that [N 1,1,1,n ] + will displace ionic liquid cations at the surface, while [C n OSO 3 ] À will displace ionic liquid anions at the surface.…”
Section: Structures At Interfacesmentioning
confidence: 99%
“…In addition, a VersaSTAT 4 potentiostat was employed to characterize the electrical performance of these two-electrode EDLC cells. It was found that the vibration mode of the CTAB head group was shifted due to the interaction with EMI-TFSI, implying the Coulombic or ion exchange interactions between the CTAB and EMI-TFSI [ 17 ]. Furthermore, the X-ray results revealed an interlayer distance of 0.41 nm as a result of CTAB intercalation in between the TRGC sheets.…”
Section: Introductionmentioning
confidence: 99%